Evaluation of laparoscopic versus open sacrocolpopexy for vaginal vault prolapse – A study from a tertiary care center - Senthilkumar Poovathai; Rajkumar Ramakrishnan; Rajasekar Sundaram; Sammohit Gulakavarapu; Gopu Rakesh Vamsi; Shravankumar Savadatti (Asian Journal of Medical Sciences, 2023)
Background: Post hysterectomy vault prolapse is a progressive herniation of the vaginal vault through the urogenital diaphragm and commonly leads to per vaginal bulge. Surgically, vault prolapse is corrected by sacrocolpopexy which can be done both as an open abdominal surgery and as a laparoscopic repair.